2019
DOI: 10.1111/fwb.13287
|View full text |Cite
|
Sign up to set email alerts
|

The effects of land use disturbance vary with trophic position in littoral cichlid fish communities from Lake Tanganyika

Abstract: Impacts of anthropogenic disturbance are especially severe in freshwater ecosystems. In particular, land use disturbance can lead to increased levels of pollution, including elevated nutrient and sediment loads whose negative impacts range from the community to the individual level. However, few studies have investigated if these impacts are uniform across species represented by multiple trophic levels. To address this knowledge gap, we focused on Lake Tanganyika cichlid fishes, which comprise hundreds of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 90 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, cases of algal bloom, ammonium buildup, increased level of suspended solids, and decreased water clarity (increased turbidity) and pH have been reported (Pitta et al, 2006;Degefu et al, 2011;Verdegem, 2013;Karikari et al, 2016;. The water quality status of various African lakes has been sufficiently studied, with most studies showing that these waters are increasingly organically polluted over the years (Helmer and Hespanhol, 1997;Odada et al, 2003;Branchu et al, 2005;UNEP, 2010;Ouma et al, 2016;Britton et al, 2019). Among other causes of this pollution, floating cages have been mentioned mainly in Lakes Volta (Clottey et al, 2016;Osei et al, 2019), Victoria (Nyakeya et al, 2022) and Kariba (Mhlanga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cases of algal bloom, ammonium buildup, increased level of suspended solids, and decreased water clarity (increased turbidity) and pH have been reported (Pitta et al, 2006;Degefu et al, 2011;Verdegem, 2013;Karikari et al, 2016;. The water quality status of various African lakes has been sufficiently studied, with most studies showing that these waters are increasingly organically polluted over the years (Helmer and Hespanhol, 1997;Odada et al, 2003;Branchu et al, 2005;UNEP, 2010;Ouma et al, 2016;Britton et al, 2019). Among other causes of this pollution, floating cages have been mentioned mainly in Lakes Volta (Clottey et al, 2016;Osei et al, 2019), Victoria (Nyakeya et al, 2022) and Kariba (Mhlanga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Ouma et al (2016) using physico-chemical parameters showed that the littoral waters in Lake Victoria were polluted, rendering them unfit for human consumption, who use them for their various domestic needs. Donohue and Irvine (2003), using the same approach, showed that in Lake Tanganyika, the physico-chemical pollution of the littoral waters due to contamination from its watershed has caused a decline in the biodiversity of this area, biodiversity that served as a source of food for pelagic fish that come here to reproduce (Britton et al, 2019). So, a water quality survey program is necessary for monitoring the water bodies' safety and freshness (Pesce & Wunderlin, 2000).…”
Section: Introductionmentioning
confidence: 99%